Precariedad, materia en deterioro y subjetividades destituidas: acerca de una «estética de la descomposición» en dos documentales de Heddy Honigmann - Dajes Kaufman, Talía (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
This essay approaches the work of Peruvian- Dutch documentarian Heddy Honigmann by analyzing two of her films Metal and Melancholy (1994) and Oblivion (2008), both set in Lima and centered on the precarious survival of its subjects. The text proposes to interpret each documentary’s visual language as the embodiment of what could be conceptualized as an «aesthetics of decomposition», thatis, the on-screen placement of objects undergoing a process of decay. I argue that, by pointing the camera toward these, the director exposes the economic and political circumstances that led to the gradual disintegration of individual and collective life conditions, as well as the erosion of the benefits previously enjoyed by middle class populations in Peru. By concentrating on the materiality of deteriorating objects, this article aims to connect Honigmann’s viewpoint with the effects that the implementation of neoliberalism may have over a paradigmatic subjectivity that can be conceived as dispossessed.

Este ensayo se aproxima al trabajo de la documentalista peruano-holandesa Heddy Honigmann a través de dos de sus producciones Metal y melancolía (1994) y El olvido (2008), situadas en Lima y centradas en la precaria subsistencia de sus personajes. El texto plantea una interpretación de sus respectivas propuestas visuales partiendo de la conceptualización de una «estética de la descomposición», es decir, de la puesta en escena de objetos en proceso de desgaste. Al apuntar la cámara hacia estos, la directora expone las circunstancias económicas y políticas que llevaron a la progresiva desintegración de las condiciones de vida individuales y colectivas, así como a la erosión de los beneficios de los que gozaban las clases medias en el Perú. Centrándose en la materialidad de los objetos en deterioro, este trabajo propone conectar el enfoque de Honigmann con los efectos de la implementación del neoliberalismo en un tipo de subjetividad paradigmática que podría concebirse como destituida.
Precariousness, Deteriorating Matter and Dispossessed Subjectivities: On the «Aesthetics of Decomposition» in Two Documentaries by Heddy Honigmann
Keywords: Teléfonos celulares; WhatsApp; Metodología mixta y digital; Sismos; Solidaridad; México; https://purl.org/pe-repo/ocde/ford#5.09.01